Eliciting requirements for designing self-reflective visualizations: A healthcare professional perspective - Visvalingam A.; Dhillon J.S.; Gunasekaran S.S.; Hoe A.C.K. (Springer, 2023)
Flow visualization; Intelligent computing; Visualization; Attitude change; Design factors; Health care professionals; Self reflection; Self-care; Self-reflective; Semi structured interviews; Thematic analysis; Health care